Avaliação da percepção temporal dinâmica de produtos alimentares mais saudáveis e emoções evocadas por consumidores do Brasil e da Espanha - Olegario, Lary Souza (2021)
The association of food consumption and health promotion often goes against the sensory expectations of consumers regarding products considered healthier. The perception of health depends on the consumer's cultural and eating habits. More realistically understanding the sensory perception of consumers from dynamic temporal evaluations, as well as the emotions generated by the stimulus of different food categories by different cultures, can provide valuable information to the industrial sector. In this context, two experiments were carried out: the first aimed to evaluate the acceptability and dynamic temporal perception of four categories of commercial foods and their healthier versions; the second aimed to return the emotional lexicon evoked by three food categories with consumers from different cultures (Brazil and Spain) and evaluate the emotional responses evoked by the stimuli of healthier versions and in view of an adequate consumption context for each culture. In the first study, 23 participants were familiarized with the establishment of a protocol for the assessment of Temporal Dominance of Sensations (TDS) with a multiple intake approach for the categories of coffee, chocolate, potato chips and yogurt. These products were evaluated in traditional and healthier versions (total or partial reduction of sugar, caffeine, lactose or fat) followed by an acceptability assessment. The parameters of time and duration of each attribute and acceptability were evaluated by ANOVA and Tukey (p<0.05) and data from the TDS curves and TDS difference curves. For the chocolate category, the increase in cocoa and the reduction in the lactose content mainly influenced the dominance of the sweetness, milk, cocoa, crunchy and bitter attributes. The absence of caffeine or added sugar in coffee with milk modified the temporal perception of sweetness, bitterness, coffee flavor and silk texture. The reduction of fat in potato chips influenced the temporal dynamic profile, highlighting the dominance of the attributes dryness, crispness, potato flavor and saltiness, and presenting higher dominance values for the texture attributes (residue, dryness and crispness) when compared to the samples classics. Lactose-free yogurt resulted in sensory characteristics similar to classic yogurt, except when considering intakes. For both chocolate and coffee, there was a positive impact on the acceptability of reformulated products, while for potato chips and yogurt there was no influence. In the second study, emotional terms associated in previous studies were collected in the categories of chocolate, potato chips and yogurt products. In total, 437 Brazilians and 397 Spaniards participated in the online survey with visual food stimuli and were asked to indicate, using the CATA (Check-All-That-Apply) method containing the emotional lexicon validity for each culture, the emotions evoked, and the most frequent consumption occasions in four dimensions (time of consumption, location, social environment and state of hunger). Sociodemographic data, liking and frequency of consumption, and level of health consciousness were also collected and statistically evaluated. The evoked emotional lexicon was different for each food stimulus and clearly influenced by the cultural factor. Brazilians associated more emotional terms more often to all stimuli than Spaniards. However, there are more similarities between cultures when evaluating the same product category. The evoked contexts were assessed as appropriate and influenced the frequency of citation of some emotional terms, including positive ones. Both cultures showed health consciousness close to “lightly agree”, a higher level of consumption, acceptability and purchase intention, and a higher frequency of positive emotional terms for the stimuli of conventional products and lower for their healthier versions.